Assessment of regional-scale water resources carrying capacity based on fuzzy multiple attribute decision-making and scenario simulation. (November 2021) - Zuo, Qiting; Guo, Jiahang; Ma, Junxia; Cui, Guotao; Yang, Rongxue; Yu, Lei
Graphical abstract: Highlights: 22 indicators were used to assess water resources carrying capacity (WRCC). Several scenarios with different weight-allocation modes were conducted. Results can provide different decision makers with suggestions for improving WRCC. Abstract: This study associates the fuzzy multi-attribute decision making (FMADM) and the analytic hierarchy process (AHP) to assess the water resources carrying capacity and to tackle uncertain problems of multiple subsystems during its evaluation. For this purpose, the water resources carrying capacity evaluation index system is proposed, and the AHP-FMADM is used to evaluate the water resources carrying capacity of 15 areas in Xinjiang Uygur Autonomous Region from 2004 to 2017. Several scenarios with different weight-allocation modes are also conducted to study the influence of decision-makers' preferences on target level. Results show that the water resources carrying capacity of all areas have been gradually improved. Overall, the economic and social indexes present an oscillation pattern with a rising, falling, and rising trend simultaneously in the study period from 2004 to 2017. The water resource utilization index varies with the amount of precipitation and reaches its peak in 2010. The ecological environment index depicts a diminishing overall trend initially before reaching a turning point in 2014. Increasing the water resources utilization and controlling rapid population growth can improve the water resources carrying capacity. The AHP-FMADM can help decision-makers to determine management plans based on their preferences, and the results of the study may contribute towards improving water resources carrying capacity.